Profile Of Tourist Visits In Sangiran Site Area, Sragen Regency - Subanti, Sri; Slamet, Isnandar; Sulandari, Winita; Zukhronah, Etik; Sugiyanto, Sugiyanto; Susanto, Irwan (Journal of Mathematics and Mathematics Education, 2021)
Tourism activities are chain activities that involve various sectors and related institutions. Tourism is one of the fields in the lives of the people of Sragen Regency, which has become one of the priorities in development in recent years. This is based on the local government's awareness that tourism development can support regional income while at the same time increasing the standard of living of people living in tourist areas. For this reason, evaluating the impact of tourism in an area on the socioeconomic conditions of the community is an important thing to know. Sangiran is one of the most complete paleontological sites in Indonesia. Sangiran has also been designated as a cultural heritage by UNESCO on December 5, 1996, with the designation number C.593. The Sangiran site itself is located in Sragen Regency and Karanganyar Regency, Central Java Province. In general, the background of the population in the Sangiran Site area comes from the Javanese ethnic group, who in daily life communicate using the Javanese language. The Sangiran site has been known as an ancient human area from the Pleistocene. Not only storing archaeological wealth, but Sangiran is also very rich in artistic potential, both from prehistoric times and the present. Many things can be enjoyed in Sangiran. Apart from the museum that presents archaeological findings full of meaning, the public can also enjoy the local culture, including traditional arts, traditional ceremonies, local architecture, and folk crafts, adding value to the site. This study aims to determine the profile of tourist visits in the Sangiran Site Area. This study found that the factors that influence the number of visits to the Sangiran Site Area are travel costs, age, gender, and monthly income of respondents related to visiting the Sangiran Site Area. Furthermore, the factors that influence the respondents' willingness to accept ticket offers in the market hypothesis scenario in the Sangiran Site Area are the nominal price of the entrance ticket to a market hypothesis given to respondents, age, gender, monthly income of respondents, education level of respondents, and origin of the respondent.